Beyond biofatalism : human nature for an evolving world - Barker, Gillian (Columbia University Press, 2015)
Beyond Biofatalism is a spirited response to the pessimism of mainstream evolutionary psychology, which argues that human beings are incapable of building a more inclusive, cooperative, and egalitarian society. Considering the pressures of climate change, unsustainable population growth, increasing income inequality, and religious extremism, this attitude promises to bury us before we even try to meet these threats. Beyond Biofatalism provides the perspective we need to understand that better societies are not only possible but actively enabled by human nature. Though she takes issue with the.